Bloodlines - Book 1 - Mead, Richelle (New York, N.Y. : Razorbill, 2011)
When alchemist Sydney is ordered into hiding to protect the life of Moroi princess Jill Dragomir, the last place she expects to be sent is a human private school in Palm Springs, California. But at their new school, the drama is only just beginning.
Series statement from author's website at http://www.richellemead.com/books/books.htm on 20 June 2011 (Bloodlines series).
Accelerated Reader AR
Keywords: Vampires -- Juvenile fiction; Private schools -- Juvenile fiction; High schools -- Juvenile fiction; Friendship -- Juvenile fiction; Princesses -- Juvenile fiction; Palm Springs (Calif.) -- Juvenile fiction